Scalability in Ad Hoc Networks:The Effects of its Complex Nature - Lopez, Juan; Trivino, Jorge (International Journal of Engineering and Technology, 2014)
One of the expected properties of the ad hoc networks is the ability to increase its size to receive new nodes and configure new applications without affecting the quality of services. This property, called scalability is affected by the decentralized nature of ad hoc networks making it necessary to develop mechanisms that allow a large number of nodes work together without affecting network performance. The following article describes how the scalability of the ad hoc networks are directly related to routing algorithms, the need of cooperation, competition for resources, the network architecture and the heterogeneous nature of the nodes.Keywords: Ad Hoc Networks, Network architecture, Game Theory, Scalability.